2021
DOI: 10.1186/s40814-021-00876-2
|View full text |Cite
|
Sign up to set email alerts
|

Mentalization-based treatment for adolescents with conduct disorder (MBT-CD): protocol of a feasibility and pilot study

Abstract: Background Conduct disorder (CD) is a complex mental disorder characterized by severe rule-breaking and aggressive behavior. While studies have shown that several therapeutic interventions are effective in treating CD symptoms, researchers call for treatments based on etiological knowledge and potential patho-mechanisms. Mentalization-based treatment (MBT) may represent such a treatment approach: Studies have shown that individuals with CD show mentalizing deficits and that mentalizing might re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Mentalization has been found to have a mediating effect on aggression ( Schwarzer et al, 2021 ), which is a common characteristic among individuals with a psychopathic personality ( Dolan and Doyle, 2000 ; Monahan et al, 2001 ; Hare and Neumann, 2008 ; Leistico et al, 2008 ). In the MBT trial on conduct disorder in Germany, psychopathy is not an exclusion criterium ( Taubner et al, 2021 ). Perhaps focusing on mentalization can be beneficial when treating individuals with psychopathy too.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentalization has been found to have a mediating effect on aggression ( Schwarzer et al, 2021 ), which is a common characteristic among individuals with a psychopathic personality ( Dolan and Doyle, 2000 ; Monahan et al, 2001 ; Hare and Neumann, 2008 ; Leistico et al, 2008 ). In the MBT trial on conduct disorder in Germany, psychopathy is not an exclusion criterium ( Taubner et al, 2021 ). Perhaps focusing on mentalization can be beneficial when treating individuals with psychopathy too.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is an ongoing multicenter RCT in London investigating MBT-ASPD’s effectiveness for male offenders compared to probation as usual ( Fonagy et al, 2020 ). MBT has also developed a program for youth with conduct disorder (MBT-CD), promising results have been published from the feasibility study ( Hauschild et al, 2023 ) and there is an ongoing RCT on MBT-CD in Germany ( Taubner et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This single-arm feasibility study was conducted between September 2016 and December 2021 at outpatient departments in Heidelberg (Institute for Psychosocial Prevention of the University Hospital Heidelberg, Centre for Psychosomatic Medicine) and Mainz (Rheinhessen Fachklinik, Department of Child and Adolescent Psychiatry and Psychotherapy of the University Medical Centre Johannes Gutenberg University Mainz), Germany. The study design and procedure are outlined in detail in the study protocol [ 25 ]. MBT-CD was delivered by therapists who were in or already finished psychotherapy training and who participated in an MBT-CD training conducted by the last author in Heidelberg (ST) and by the last and first author (ST & SH) in Mainz.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescents received a total of 50€ for taking part in the scientific assessments. An overview of study flow and measures can be found in the study protocol by Taubner et al [ 25 ] (Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Less perceptual, but more complex, mental approaches focused on procedural and executive mental functions and social skill trainings to control impulsive behaviors ( 10 ). Talia et al followed an approach based on emotional empathic skills, such as epistemic trust and its role in the understanding of aggression in conduct disorder.…”
mentioning
confidence: 99%